High School Completion Programs: A Community Guide Systematic Economic Review. Issue 3 (May 2016) - Qu, Shuli; Chattopadhyay, Sajal K.; Hahn, Robert A.
Abstract : Context: On-time high school graduation rate is among the 26 leading health indicators for Healthy People 2020 . High school completion (HSC) programs aim to increase the likelihood that students finish high school and receive a high school diploma or complete a GED (General Educational Development) program. This systematic review was conducted to determine the economic impact of HSC interventions, assess variability in cost-effectiveness of different types of programs, and compare the lifetime benefit of completing high school with the cost of intervention. Evidence Acquisition: Forty-seven included studies were identified from 5303 articles published in English from January 1985 to December 2012. The economic evidence was summarized by type of HSC program. All monetary values were expressed in 2012 US dollars. The data were analyzed in 2013. Evidence Synthesis: Thirty-seven studies provided estimates of incremental cost per additional high school graduate, with a median cost for HSC programs of $69 800 (interquartile interval = $35 900-$130 300). Cost-effectiveness ratios varied depending on intervention type, study settings, student populations, and costing methodologies. Ten studies estimated the lifetime difference of economic benefits between high school nongraduates and graduates; 4 used a governmental perspective and reported benefit per additional high school to range from $187 000 to $240 000; 6 used a societal perspective and reported a range of $347 000 to $718 000. Benefits exceeded costs in most studies from a governmental perspective and in all studies from a societal perspective. Conclusion: Interventions to increase HSC rates produce substantial economic benefits to government and society including averted health care costs. From a societal perspective, the benefits also exceed costs, implying a positive rate of return from investment in HSC programs. Abstract : This article determines the economic impact of high school completion interventions, assesses variability in cost-effectiveness of different types of programs, and compares the lifetime benefit of completing high school with the cost of intervention.